Environmental and Biological Determinants of Brain Mass - Kevin Yunqin Zhang (BIO Web of Conferences, 2023)
According to the expensive brain hypothesis, periodic energy level determines the brain mass. However, various environmental and biological factors directly or indirectly relevant to energy intake have not been well studied. Here, we systematically examined how body mass, hibernation, diurnally, substrate use, diet individually and synergistically determine brain mass in a large dataset of more than 1000 species. We found that body mass and hibernation are the major determinants of brain mass in most species. These findings will shed light on future studies of how evolutionary constraints acting on brain size.